Definition of a System of Management of Domestic Solid Residues with Compostagem -Londrina, PR - Moares, Renato Pianowski de; Zapparoli, Irene Domenes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The research aims at to analyze the insertion of the compostagem as central element for proposals of systems of integrated management of solid residues in the city of Native of London, Paraná. Considering the agricultural characteristics of Brazil, the considered model presentes perspectives of exploitation of these residues in all country. From a survey of the potentialities of this modality of treatment of residues, in face of the predominance of organic components, in the generation of urban solid residues, and of the agricultural vocation of Brazil, technique in the integrated systems of management of residues searchs to analyze elements for the application of this. Amongst the elements considered in this evaluation, the decurrent ambient benefits of this modality are distinguished in such a way, as the economic, social aspects and the motivation that this technique offers for the ambient awareness. It enters the presented limitations generically meet it low attractiveness of the comparative composition to competing chemical fertilizers, in what it says respect to the effectiveness of these in the agricultural use; the availability of areas for implantation of some techniques of compostagem, particularly most rustic, that demand much hand of workmanship, beyond the inherent problems to the demanded handling. Valley to detach that the compostagem has been systematically white of lobbies of the chemical fertilizer sector and the proper companies of garbage landing, a time that the diffusion of this technique represents a threat to these markets.